2006
DOI: 10.1177/1077559505285747
|View full text |Cite
|
Sign up to set email alerts
|

Discipline Practices Among Biological and Foster Parents

Abstract: In a sample of 124 parents (62 pairs of biological and foster parents) of children who were maltreated (M age = 6.2 years), this study compared self-reports of discipline practices between biological and foster parents toward a target child and explored the role of child, parent, and foster care ecology factors on discipline practices. Controlling for parental age, psychological distress, and marital status, biological and foster parents reported using similar levels of positive, appropriate, and harsh discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…Foster homes with the highest relationship satisfaction (Orme et al 2004) lowest relationship stress (Lipscombe et al 2004) and highest ratings of parent-to-parent cooperation were the most successful (Linares et al 2006b).…”
mentioning
confidence: 99%
“…Foster homes with the highest relationship satisfaction (Orme et al 2004) lowest relationship stress (Lipscombe et al 2004) and highest ratings of parent-to-parent cooperation were the most successful (Linares et al 2006b).…”
mentioning
confidence: 99%
“…It is difficult to determine whether the differences obtained in this study reflect response bias (i.e., under reporting of behavior) or actual disciplinary practices of foster parents. The literature is inconsistent in its findings regarding foster mother discipline practices, with some studies reporting greater use of harsh discipline by foster mothers (Linares et al, 2006) and others reporting the use of noncorporal disciplinary practices with their foster children, though the same foster mother produced harsh disciplinary responses to hypothetical situations (Tripp De Robertis & Litrownik, 2004). However, foster mother responses on the other parenting behavior scales (i.e., nurturing and expectations) provide some evidence that the data reflect actual behavior rather than a response bias.…”
Section: Discussionmentioning
confidence: 97%
“…As the authors noted, the foster mothers indicated they preferred to use teaching and limit setting as their primary disciplinary practices when dealing with their foster child's problematic behavior. In an interesting study comparing biological and foster mothers' discipline practices (Linares, Montalto, Rosbruch, & Li, 2006), there were no differences found between biological and foster mothers in their use of positive, appropriate, and harsh discipline; however, foster mothers reported higher expectations than did biological mothers. The authors also found a significant relationship between foster mother's harsh discipline, high expectations, and child behavior problems, which the authors noted may reflect the foster mother's response to the difficult characteristics of the foster child.…”
mentioning
confidence: 99%
“…Onderzoek naar het opvoedgedrag van pleegouders en de effecten ervan op de ontwikkeling van de pleegkinderen is nauwelijks voorhanden (Linares, Montalto, Rosbruch & Li, 2006). Onderzoek toont wel dat pleegouders kunnen leren om op een positieve manier met het probleemgedrag van hun pleegkind om te gaan en dat dit resulteert in een afname van het probleemgedrag (Fisher, Gunnar, Chamberlain & Reid, 2000;Linares e.a., 2006) en/of minder breakdowns (Fisher, Burraston & Pears, 2005;Kalland & Sinkkonen, 2001).…”
Section: Inleidingunclassified